PERSEPSI KINERJA GURU, DITINJAU DARI PERSEPSI DUKUNGAN ORGANISASI, PERSON-ORGANIZATION FIT, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fenny Soeprijadi; Niko Sudibjo (Jurnal Pendidikan, 2021)
Teachers’ performance will improve with the support of the school, compatibility between teacher as an individual with the values, goals, and characteristics of the organization. Teachers’ behavior will also contributes positively to improving performance.This study was aimed to determine the effect of perceived organizational support, person-organization fit, and organizational citizenship behavior on the performance of Kairos Gracia School teachers in West Jakarta. This research used quantitative approach and PLS-SEM method for data analysis. Data was collected by distributing questionnaires and analyzed descriptively and inferentially by conducting validity, reliability, and path analysis tests by using SmartPLS 3.2.9. software. The results showed that perceived organizational support did not have a direct positive influence on teachers performance, while person-organization fit and organizational citizenship behavior have a positive effect on performance. Perceived organization support would be positively influenced teachers’ performance when mediated by organizational citizenship behavior. Kinerja guru akan meningkat dengan adanya dukungan dari pihak sekolah, kecocokan antara guru sebagai individu dengan nilai, tujuan, dan karakteristik organisasi Perilaku guru juga memberikan kontribusi positif terhadap peningkatan kinerja. Penelitian ini bertujuan untuk mengetahui pengaruh persepsi dukungan organisasi, person-organization fit, dan organizational citizenship behavior terhadap kinerja guru Sekolah KARIOS GRACIA di Jakarta Barat. Penelitian ini. bersifat kuantitatif. Data dikumpulkan melalui kuesioner dan dianalisis secara deskriptif dan inferensial untuk uji validitas, reliabilitas, dan analisis jalur dengan metode PLS-SEM melalui program SmartPLS 3.2.9. Hasil penelitian menunjukkan bahwa persepsi dukungan organisasi secara langsung tidak memiliki pengaruh positif terhadap kinerja guru. sedangkan person-organization fit dan organizational citizenship behavior berpengaruh positif terhadap kinerja. Persepsi dukungan organisasi akan memiliki pengaruh positif terhadap kinerja guru melalui variabel laten organizational citizenship behavior.